2023
DOI: 10.1021/acs.molpharmaceut.3c00090
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Protein–Protein Interactions and Liquid–Liquid Phase Separation for Monoclonal Antibodies

Abstract: Being able to predict and control concentrated solution properties for solutions of monoclonal antibodies (mAbs) is critical for developing therapeutic formulations. At higher protein concentrations, undesirable solution properties include high viscosities, opalescence, particle formation, and precipitation. The overall aim of this work is to understand the relationship between commonly measured dilute solution parameters, the reduced osmotic second virial coefficient b 22 and the diffusion interaction paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…The calculated b 2 * for the AS-free solution matches well with prior measurements of ovalbumin . Mapping interaction data in terms of the reduced coefficient b 2 * rather than B 22 allows for a comparison of interaction strength with data in the literature for other protein systems. , …”
Section: Methodssupporting
confidence: 73%
“…The calculated b 2 * for the AS-free solution matches well with prior measurements of ovalbumin . Mapping interaction data in terms of the reduced coefficient b 2 * rather than B 22 allows for a comparison of interaction strength with data in the literature for other protein systems. , …”
Section: Methodssupporting
confidence: 73%
“…Much effort has been directed toward understanding the impacts of formulating high-concentration drugs on stability and protein particle formation. Previous studies include the development of experimental and molecular simulation techniques to understand how intermolecular protein interactions impact clustering and aggregation at high protein concentrations. , , However, most studies involving high concentrations of protein therapeutics are devoted to studying bulk solutions. Thus, the interfacial behavior of protein films formed in concentrated mAb solutions is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this discovery is that it allows a multi-protein action (crystallization) to be simplified through modeling, only requiring understanding of the first step, namely, the protein-protein pair interaction, measured by the second virial coefficient. Other binary coefficients, such as k D , obtained from dynamic light scattering [54,55] and the Huggins viscosity coefficient [56], have proven to be very informative as well. For example, it has been shown that, as with B 22 , k D is correlated with the cloud point temperature, which determines the two-phase region in protein solutions [57].…”
Section: Background On Modeling the Forces In Protein Solutionsmentioning
confidence: 99%